Prosedur Pemberian Sertifikat Label Halal Terhadap Produk Makanan Di Restoran Hotel Syariah Untuk Mewujudkan Hak Kenyamanan Konsumen Muslim (Studi Di Kementerian Agama Provinsi Sumatera Utara) - Mukidi Mukidi (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
Businessmen have the duty of ensuring halal food products and giving the halal label on the basis of having obtained a halal certificate from the ministry of religion which was socialized to the consumer society in a way that it is conveyed through writings that are easy to read and not easily removed by a visitor at a particular place in the restaurant. It is according to Article 39 of Law Number 33 Year 2014 concerning the guarantee of halal products. The halal certificate is valid for four years since it was issued by the Halal Product Guarantee Agency (HPGA), and it must be extended. Halal certificates are mandatory, so the food products which do not have halal label certificate cannot longer circulate in Indonesia.The procedure for obtaining halal certification at the hotel restaurant which was issued by the Ministry of Religious Affairs (MORA). First, businessmen must fulfill the requirements which were checked by HPGA such as, the data  of businessmen, the name and type of business product, a list of products and materials used, the manner or the product processing as well as halal guarantee system. After fulfilling the requirements of HPGA in checking the dokumen, then determine the LPH that has been selected by the applicant, then the LPH conducts the examination and / or testing of the next step of the MUI product through the determination of the halal food product halal through a halal fatwa session. After the process is carried out through the prescribed stages, the HPGA issues a halal certificate.Keywords : Halal Label Certification, Halal Products, Halal Product Protection Guarantees